(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Generally speaking postoperative nausea and vomiting (PONV) as the most conventional complaint afterward anesthesia that can attend the desolation like bleeding, electrolyte disorders, gastric content aspiration as well as delay hospital remittance. Postoperative emesis where as has a high incidence even though the extensive whole of research done in this field and the variety of antiemetic drugs accessible. In order to manage this crisis, they need a multi approach which can include the certified analgesia, emetogenic anesthetic techniques as well as appropriate intravenous hydration. The current study aims to assess the postoperative nausea and vomiting incidence for pediatric undergoing surgical operations. A total number of 140 patients (74 male and 66 female) with age ranges (6-12) years old, duration of surgery equals or less than 30 min and body mass index less than 30 . General anesthesia is achieved for admitted elective patients. All patients are confirming according the questions of questionnaire; we monitor the incidence of nausea and vomiting in the recovery room. We conclude that the patients with (30%) have an incidence of nausea and vomiting postoperatively that may be related by causes (age, history of PONV, anxiety , type of operation and anesthetic drug).and patients with (70%) have no nausea and vomiting incidence postoperatively that may be related by causes (sex, obesity and inhalation agents).